The role of magnesium in the secondary phase after traumatic spinal cord injury: a prospective clinical observer study - Sperl, André; Heller, Raban; Biglari, Bahram; Haubruck, Patrick; Seelig, Julian; Schomburg, Lutz; Bock, Tobias; Moghaddam-Alvandi, Arash (Antioxidants, 2019)
In the secondary injury phase after traumatic spinal cord injury (TSCI), oxidative stress and neuroinflammatory responses at the site of injury constitute crucial factors controlling damage extent and may serve as potential therapeutic targets. We determined Magnesium (Mg) serum concentration dynamics in context with the potential of neurological remission in patients with TSCI as Mg is suspected to limit the production of reactive oxygen species and reduce lipid peroxidation. A total of 29 patients with acute TSCI were enrolled, and blood samples were drawn over 3 months at 11 time-points and Mg quantification was performed. Patients were divided into those with (G1, n = 18) or without neurological remission (G0, n = 11). Results show a slight drop in Mg level during the first 4 h after injury, then remained almost unchanged in G1, but increased continuously during the first 7 days after injury in G0. At day 7 Mg concentrations in G1 and G0 were significantly different (p = 0.039, G0 > G1). Significant differences were detected between patients in G1 that presented an AIS (ASIA Impairment Scale) conversion of 1 level versus those with more than 1 level (p = 0.014, G1 AIS imp. = +1 > G1 AI imp. > +1). Low and decreasing levels of Mg within the first 7 days are indicative of a high probability of neurological remission, whereas increasing levels are associated with poor neurological outcome.
Gesehen am 26.02.2020